ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUNTARY AUDITOR SWITCHING DI PERUSAHAAN MANUFAKTUR INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2008-2012) - Nurin Ari Fitriani; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to find empirical evidence on the factors that influence the voluntary auditor switching in Indonesia. These factors are client’s size, company's growth, financial distress, audit opinion, management turnover, and client’s complexity. This topic was chosen because many companies in Indonesia switch the auditor voluntarily not accordance with government regulations.This research uses financial statement data of companies listed in Indonesia Stock Exchange (BEI) in the period of 2008-2012. Data collecting method which used in this research is purposive sampling. 57 manufacturing companies are used as samples. Hypothesis are tested by logistic regression analysis. The result showed that company's growth (GROWTH), financial distress (DAR), and client’s complexity (SUBS) affected voluntary auditor switching, while client’s size (CLIENTSIZE), audit opinion (OPINI), and management turnover (CEO) have no association and effect significantly.